2017
DOI: 10.1007/s10096-017-3118-1
|View full text |Cite
|
Sign up to set email alerts
|

Extensive colonization with carbapenemase-producing microorganisms in Romanian burn patients: infectious consequences from the Colectiv fire disaster

Abstract: Health care of severe burn patients is highly specialized and may require international patient transfer. Burn patients have an increased risk of developing infections. Patients that have been hospitalized in countries where carbapenemase-producing microorganisms (CPMO) are endemic may develop infections that are difficult to treat. In addition, there is a risk on outbreaks with CPMOs in burn centers. This study underlines that burn patients may extensively be colonized with CPMOs, and it provides best practic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 54 publications
0
12
0
1
Order By: Relevance
“…bla OXA-48, bla KPC-2, bla NDM-1 and bla OXA-162 ) found in the majority of the influent, effluent and clinical isolates are those reported as prevalent both in Romania and in other geographical areas [29]. Previous studies performed in Romania on carbapenem-non-susceptible Klebsiella pneumoniae clinical isolates have shown that bla OXA-48 was by far the most predominant genotype, followed by bla NDM-1 and bla KPC-2 [30,31,32]. The corresponding STs for the carbapenemase-producing isolates are: ST101 and ST258 (the most prevalent, as also reported in other studies including those performed on Romanian clinical strains by the authors of the present paper [11,33], followed by ST11, ST17, ST219, ST307 and ST395).…”
Section: Discussionmentioning
confidence: 82%
“…bla OXA-48, bla KPC-2, bla NDM-1 and bla OXA-162 ) found in the majority of the influent, effluent and clinical isolates are those reported as prevalent both in Romania and in other geographical areas [29]. Previous studies performed in Romania on carbapenem-non-susceptible Klebsiella pneumoniae clinical isolates have shown that bla OXA-48 was by far the most predominant genotype, followed by bla NDM-1 and bla KPC-2 [30,31,32]. The corresponding STs for the carbapenemase-producing isolates are: ST101 and ST258 (the most prevalent, as also reported in other studies including those performed on Romanian clinical strains by the authors of the present paper [11,33], followed by ST11, ST17, ST219, ST307 and ST395).…”
Section: Discussionmentioning
confidence: 82%
“…In a previous study, we demonstrated the antibacterial effect of the BGAuIND against multi-drug resistant Pseudonomas aeruginosa and Staphyloccoccus aureus [ 12 ]. Considering that the burn patients have an increased risk of developing infections and the Pseudomonas aeruginosa is a type of germ present in hospitals [ 23 ], the viable strategy would be to use the ointments with BGAuIND to treat these patients. Thus, a study of this possible application is the subject of a future study.…”
Section: Resultsmentioning
confidence: 99%
“…Presently Imipenem ,Vancomycin ,Netilmicin and Linizolid are effective for drug resistant pathogen, however there must be controlled use of these resourceful antibiotics. [7][8][9] Potz etal study stated that, while resistance to multiple antibiotics limits the therapeutic options for infections with ESBL-producing organisms, none of the isolates in their study showed resistance to Imipenem or Meropenem. It is therefore comforting to observe the continuing efficacy of the carbapenems against problematic isolates.…”
Section: Discussionmentioning
confidence: 96%